Pelatihan Pembuatan soal bagi Guru SMK Kepariwisataan di Kabupaten Bandung Barat - Ridwanudin, Oce; Suwandi, Andreas; Ardhita, Mayadisa (Rumah Jurnal UNEJ, 2022)
This community service activity aims to provide an understanding of the characteristics and ways to develop quality HOT (Higher Order Thinking) questions, provide direct experience in transforming ordinary questions into HOT questions and in developing HOT questions for students. Tourism teacher at SMK in West Bandung Regency. The target of PPM is vocational tourism teachers in West Bandung Regency who were selected by random sampling, meaning that one teacher is selected from several tourism teachers in each Vocational School in West Bandung Regency. PPM will be held on Friday 03 September 2021 at SMK Bina Wisata Lembang with lecture, discussion, and question and answer methods on issues related to developing HOT questions, as well as practice converting LOTS questions into HOT. responsibility in a row in the categories of good, very good, and good. The assessment of mastery of HOT questions through independent assignments changes the MANY questions into HOT questions. In general, this PPM activity was successful and on target, as evidenced by the participants who were very enthusiastic about participating in the activity from beginning to end and all participants stated that the PPM activity was beneficial. It is hoped that the participants who attend the activity can share knowledge with other teachers at their school or even other schools